Just theory : an alternative history of the western tradition - Downing, David B., 1947- (National Council of Teachers of English, 2019)
Just theory offers an alternative history of critical theory in the context of the birth and transformation of the Western philosophical tradition. But rather than providing a summary survey, it situates the production of theoretical texts within the geopolitical economy of just two pivotal cultural turns: Cultural Turn I (roughly 450-350 BCE) looks at the Platonic revolution, during which a new philosophic, universalist, and literate discourse emerged from what had long been an oral culture; Cultural Turn 2 (roughly 1770-1870) investigates the Romantic revolution and its nineteenth-century aftermath up to the Paris Commune. While focusing on the quest for social justice, David B. Downing situates the two cultural turns within deep time: Cultural Turn I gave birth to the Western philosophical tradition during the Holocene; Cultural Turn 2 witnessed the beginnings of the shift to the Anthropocene when the Industrial Revolution and the fossil fuel age began to alter our complex biospheres and geospheres. As described in the epilogue, the aftereffects of Western metaphysics have dramatically shaped our twenty-first-century world, especially for teachers and scholars in English and the humanities.